Implementation of Optical Character Recognition and Voice Recognition of House of Words (How) Dictionary Application on Android Platform - Hutami Septiana Raswaty; Nuryuliani Nuryuliani (Engineering, MAthematics and Computer Science (EMACS) Journal, 2021)
People with different languages need to be assisted by translator to establish the communication between them. The technology development which exists to fulfill communication needs is digital dictionary as translator tool. The capability of digital dictionary to translate the languages yet has a weakness in putting the input. Through this research, Optical Character Recognition using Tesseract library and Voice Recognition technologies using Google Speech-To-Text are used to replace the previous input system. Based on the implementation and testing, the OCR and Voice Recognition have been successfully recognizing the text and voice input with the amount of similarity of 92,72% for OCR and 95,46% for Voice Recognition. The result of the implementation is expected to help a group of people with different language to communicate easily.